Peran Motivasi Intrinsik, Kompensasi Dan Pengembangan Karir Terhadap Komitmen Afektif (Studi Pada Kantor Pusat Waroeng Spesial Sambal Yogyakarta) - Ahdat, Baharudin Syafril (Jurnal Manajemen DIVERSIFIKASI, 2022)
This study aims to determine (1) the role of intrinsic motivation on affective commitment, (2) the role of compensation for affective commitment, (3) the role of career development on affective commitment, and (4) the role of intrinsic motivation, compensation and career development together towards Affective Commitment. The research used is quantitative research. This research was conducted at the Head Office of Waroeng Spesial Sambal “SS”. The number of employees who are in the Waroeng SS Head Office is 100 employees, in calculating the number of respondents in this study using the Slovin formula which produces 80 respondents. The data collection method used a questionnaire and is homogeneous or free. This research uses data quality test, classic assumption test (normality test, heteroscedasticity test and multicollinearity test), multiple linear regression analysis and hypothesis testing. The results of this study indicate that the intrinsic motivation variable has a positive and significant role to the affective commitment variable. The Compensation Variable has a positive and significant role on the Affective Commitment Variable. Career Development Variable does not play a role in the Affective Commitment Variable. Intrinsic Motivation, Compensation and Career Development variables together or simultaneously affect the Affective Commitment Variable. Keywords: Affective Commitment, Intrinsic Motivation, Compensation, Career Development.